Knowledge and Behavior Relationships about Nutrition to Events Anemia in a Teenage Princess in Bulanjahe Village, District Barusjahe Karo Regency in 2019 - Hanry Anta Lesmana (Science Midwifery, 2020)
Nutrition, also known as nutrition, is the study of food and its relationship to health. This study aims to determine the relationship between knowledge and behavior about nutrition on the incidence of anemia in adolescent girls. The independent variable is knowledge and behavior about nutrition and the dependent variable is the incidence of anemia in adolescent girls in Bulanjahe Village, Barusjahe District, Karo Regency in 2019. This type of research is a pre-experiment with the design of "The One Shot Case Study". The population in this study were 30 young women who were in Bulanjahe Village, Barusjahe District, Karo Regency. The sample in this study were 30 by means of total sampling. The data collected were primary and secondary data, then the data were processed using SPSS steps and Chi-Square statistical test α = 0.05. The results showed that most of the respondents who had sufficient knowledge were 18 people (60%), 18 people (60%) had an active behavior, the majority had anemia, 12 people (40%) based on the chi-square statistical test, the value of p = 0.000 was obtained. This means that the p value is smaller than the p value (0.05) and thus Ho is rejected and Ha is accepted, namely knowledge and behavior about nutrition in adolescent girls has a significant relationship with the incidence of anemia. It is recommended to young women in Bulanjahe Village, Barusjahe District, Karo Regency in 2019 to meet the nutritional needs of the body and seek information about anemia.